Analisis Pengembangan Usaha Keripik Dangke di Kabupaten Enrekang - Abduh, M. Natsir; Mallawangeng, Tamrin (DEDIKASI, 2018)
The purpose of this study was to determine the comparison of price and value added value from dangkeproduction to dangke chips. This research was carried out for two months, from April to May 2018. The place ofresearch was on the home industry producing dangke chips and dangke production in Cendana Village, CendanaDistrict, Enrekang Regency. The method used in this research was to take primary data and secondary data. Primarydata was obtained through direct interviews using the questionnaire. Secondary data was obtained through literaturethat supports and has a relationship with this research. Data analysis was attained through the following methods,namely; 1) calculate the estimated profit of dangke production; 2) calculate the estimated profit of dangke chipsproduction; 3) comparing the difference in costs between dangke production and dangke chips production. Theresults of this study indicated that the quantity and quality of production are strongly influenced by management ofpre and post cow milk management, feeding and health of dairy cattle. The quality of dangke chips is alsoinfluenced by the quality of cow's milk and the quality of dangke as a basic ingredient. Daily profit estimated fordangke production, amounting to Rp. 300,835; and the production of dangke chips was 3,992,170. Value addedprofit or difference in estimated daily profits from the production of dangke chips and dangke production amountedto Rp. 3,691,335. In another word, the dangke chips production is more profitable than dangke production.